1997
DOI: 10.1111/j.1540-8159.1997.tb06778.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Guided Radiofrequency Catheter Ablation of Myocardium: Comparison of Catheter Tip and Tissue Temperatures In Vitro

Abstract: Temperature monitoring during RF ablation has been proposed as a means of controlling the creation of the lesion. However, in vivo studies have shown poor correlation between lesion size and catheter tip temperature. Thus, we hypothesized a difference between catheter tip and tissue temperatures during RF catheter ablation, and that this difference may depend on flow passing the ablation site, tip electrode length, and catheter-tissue orientation. In vitro studies were performed using four different ablation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 8 publications
3
44
0
Order By: Relevance
“…Transmurality of isthmus lesions was difficult to assess due to the complex anatomy of this region. There was no significant difference in endocardial surface area between standard and magnetic catheters: 39 mm 2 ). Additional lesions from the three other animals were included in the analysis of table 1.…”
Section: Macroscopic Lesion Assessment Standard Vs Magnetically Steementioning
confidence: 99%
See 1 more Smart Citation
“…Transmurality of isthmus lesions was difficult to assess due to the complex anatomy of this region. There was no significant difference in endocardial surface area between standard and magnetic catheters: 39 mm 2 ). Additional lesions from the three other animals were included in the analysis of table 1.…”
Section: Macroscopic Lesion Assessment Standard Vs Magnetically Steementioning
confidence: 99%
“…These factors have been studied extensively. [1][2][3][4][5][6] A magnetic navigation system (Niobe, Stereotaxis Inc., St. Louis, MO, USA) allows the use of floppy magnetic tip catheters, steered and advanced remotely, using an applied magnetic field and an external advancer system. These catheters may have advantages in positioning in difficult anatomy, and also in maintaining position during ablation.…”
mentioning
confidence: 99%
“…The final result is charring within the myocardium. 4,7) These events are undesirable, are associated with a risk of perforation, and may occur during cooled-tip RFCA while "low" temperatures are recorded from the catheter. We previously reported that steam pop and intramyocardial charring occurred when the temperature of the catheter tip used for cooled RF ablation exceeded 45°C.…”
Section: R Adiofrequency (Rf) Ablation Destroys Myocardialmentioning
confidence: 99%
“…Measured electrode temperature is typically restricted to 60-70°C due to the discrepancy between the temperature at the electrode, which is cooled by circulating blood, and the tissue temperature. 1,4) A saline-irrigated or "cooled" RF catheter circulates saline through the electrode tip, cooling the distal electrode and tissue interface and allowing greater energy delivery before coagulum formation and charring set in. Larger ablation lesions can thereby be created.…”
Section: R Adiofrequency (Rf) Ablation Destroys Myocardialmentioning
confidence: 99%
“…Additionally, irrigation at the site of ablation has also helped to minimize thrombus formation at the ablation site as well. The saline used for irrigation can be circulated within the electrode (closed loop system), or open irrigation system that flushes saline through openings in the ablation electrode (Budde et al 1987, Grumbrecht et al 1998, Kongsgaard et al 1997, matsudairi et al 2003, Nakagawa et al 1998, Wittkampf et al 1989and Yokoyama et al 2006. A major limitation of this catheter is the poor correlation of the tip temperature with the tissue temperature, often resulting in RF being curtailed and therefore incomplete lesions are made.…”
Section: Irrigated Tip Electrode Cathetermentioning
confidence: 99%